Hematoma subdural raquidiano - Ribeiro, M (2012)
Spinal subdural haematoma is a rare pathology and may cause severe neurological deficit. In this paper a case of acute spinal subdural haematoma of multifactorial etiology--traumatic versus iatrogenic--is presented, in which the clinical evaluation, Computerized Tomography and Magnetic Resonance were of utmost importance as far as the early diagnosis is concerned, allowing therefore decompressive surgery to avoid neurological deficit development.